Effect of EGR (exhaust gas recirculation) in diesel engine with multi-walled carbon nanotubes and vegetable oil refinery waste as biodiesel. (15th March 2021) - Manieniyan, V.; Velumani, V.; Senthilkumar, R.; Sivaprakasam, S.
Highlights: EGR technique is used to reduce the NOx emission. Vibration is measured at three different place of Engine (Head, Crank and Bottom). Vibration of Engine is reduced in MWCNT30ppmB20EEGAO with 5% EGR. Multi-walled carbon nanotubes blend with biodiesel improves engine performance and reduces emissions. HC, CO and smoke reduced with Multi-walled carbon nanotubes blend with biodiesel. Abstract: In diesel engines, emissions are the main problem. To reduce the engine emission by different methods, like as, after treatment of exhaust gases, operating parameters, design parameters, in-cylinder combustion control and fuel modification are used. This study is aimed to concurrently study the use of biodiesel blends with a multi walled carbon nanotube and EGR to minimize pollution from all diesel engine governed pollutants. The experimental investigation was conducted an analysis the emission, vibration character and the impact on the engine performance by using Exhaust Gas Recirculation (EGR) using multi-walled carbon nanotubes (MWCNT) with 20% biodiesel blend (optimum blend MWCNT30ppmB20EESAO) and diesel with various EGR ratios (5%, 10%, 15% and 20%). The engine vibration is measured at three different places, including Head, Crank and Bottom of the engine. The engine vibration is measured in terms of acceleration. The maximum brake thermal efficiency was 29.78% and lesser SFC 0.241 kg/kW-hr at EGR 5%. The EGR5% overall 2.2% is increased in BTE and 3.1% is decreased in SFC compare to the other EGR ratio. Similarly the emission parameter the NOx is reduced in 21.06% at EGR 20%, but other emission CO in 5.2%, HC in 6.2% and smoke density 4.34% at EGR 5%. The minimum acceleration was 219.11 m/sec 2 for head, 126.13 m/sec 2 for crank, and 80.54 m/sec 2 for bottom in MWCNT30ppmB20EESAO blend at 20% load.